2019
DOI: 10.1093/nar/gkz863
|View full text |Cite
|
Sign up to set email alerts
|

ZAR1 and ZAR2 are required for oocyte meiotic maturation by regulating the maternal transcriptome and mRNA translational activation

Abstract: Zar1 was one of the earliest mammalian maternal-effect genes to be identified. Embryos derived from Zar1-null female mice are blocked before zygotic genome activation; however, the underlying mechanism remains unclear. By knocking out Zar1 and its homolog Zar2 in mice, we revealed a novel function of these genes in oocyte meiotic maturation. Zar1/2-deleted oocytes displayed delayed meiotic resumption and polar body-1 emission and a higher incidence of abnormal meiotic spindle formation and chromosome aneuploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 55 publications
6
63
0
Order By: Relevance
“…Differences in maternal gene expression lead to the lower developmental potential of aged oocytes. For instance, ZAR1 plays essential role in transition from oocyte to embryo 38 , and its expression in this study was found to be reduced in aged oocytes. Furthermore, Ax treatment was helpful to maintain the maternal gene expression for C-MOS , CCNB1 , BMP15 , CDX2 and POU5F1 in aged oocytes.…”
Section: Discussionmentioning
confidence: 48%
“…Differences in maternal gene expression lead to the lower developmental potential of aged oocytes. For instance, ZAR1 plays essential role in transition from oocyte to embryo 38 , and its expression in this study was found to be reduced in aged oocytes. Furthermore, Ax treatment was helpful to maintain the maternal gene expression for C-MOS , CCNB1 , BMP15 , CDX2 and POU5F1 in aged oocytes.…”
Section: Discussionmentioning
confidence: 48%
“…Oocyte maturation and fertilization have been explored for many years [21,33,34]; however, little is known regarding the different mechanisms between human and mouse. Here, we analyzed the transcriptomes of human and mouse GV and MII oocytes to explore the differences between human and mouse oocytes at the transcriptional level [22,35].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the mechanisms of maternal mRNA decay in mouse oocytes. For example, BTG4, CNOT6L and ZAR1/2 participate in the destruction of target specific transcripts during oocyte maturation [13,34,36]. However, the differences of selectively degraded transcripts between human and mouse have not been explored in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, transcription of MuERV-L target genes, including Guca1a, Tead4, Tdpoz1/4, and Zfp352, was also blocked after maternal Pabpn1l deletion (Appendix Fig S1B). We also microinjected zygotes (WT and Pabpn1l ♀À/♂+ ) with the MuERV-L::tdTomato reporter plasmid (MuERV-L 5 0 -long terminal repeat (LTR) promoters upstream of the red fluorescent protein tdTomato) as previously described [36,38] and monitored the expression of tdTomato during culture. TdTomato expression was observed in WT 2-cell embryos but not in Pabpn1l ♀À/♂+ embryos, which arrested at the 1-to 2-cell stage (Fig 3E and F).…”
Section: Maternal Pabpn1l Is Essential For Zgamentioning
confidence: 99%